Model Pengelolaan Zakat Saham dan Investasi Di BAZNAS PROVINSI DKI JAKARTA - Fajria Nur Fitri, (2021)
Indonesia is one of the most populous Muslim countries, so it has a very large potential for zakat. Zakat in Indonesia is known as the types of zakat fitrah and zakat maal, but over time the types of zakat maal have developed which are known as contemporary zakat in the form of professional zakat, stock zakat, investment zakat, deposit zakat, and the like. Each type of zakat collected is expected to have the potential to improve the economy and prosper the people. Zakat shares in Indonesia have the distribution of funds from companies or individuals based on the results of company profits and share profits where this profit is given to mustahik. So from this research on the management of stock and investments zakat, the authors found that the related problems are still found to be low awareness of shareholders and investors to pay their zakat. This study aims to explain the model of stock and investment zakat management, and to analyze the stock and investments zakat program at BAZNAS DKI JAKARTA. The method used is a qualitative descriptive approach, the data source used are through previous research, books, and the results of interviews with sources who understand zakat shares and investments. The results obtain buy BAZNAS DKI JAKARTA PROVINCE in managing stock and investment zakat using the theory of Yusuf Qardhawi and in an effort to increase muzakki or investors, BAZNAS DKI JAKARTA Province has made efforts to disseminate information to companies and sosial media. Social media during the covid-19 pandemic has provided a significant increase.